Rhinoplasty - Guyuron, Bahman (Elsevier/Saunders, 2012)
Helping you choose and apply the best approaches for particular patient populations such as cocaine users, patients with thick skin, ethnic patients, and revision rhinoplasty patients, this title features operative animations, high-quality videos and artwork, 3D demonstrations, and instructions that provide all the guidance you need to succeed.